Strand 3: Developing Self Assessment in Networked Lifelong Learning Environments - McConnell, David (Proceedings of the International Conference on Networked Learning, 1998)
This paper is a contribution to our understanding of the development of professional practice in networked learning environments. In the paper I examine: assessment processes in networked learning environments which involve the learner, their peers and a tutor in making judgements about the learner's formal course work; the role of the tutor/teacher in these processes. I suggest that assessment should be a learning event and that networked learning course participants should be involved in making judgements about their own and their peers' learning. The benefits to learners and tutors of these collaborative learning processes are examined and discussed.